Strategi Komunikasi Humas Sekda Pemerintah Kota Semarang Melalui Penggunaan Media Sosial Instagram @Pemerintahkotasemarang dalam Publikasi Kinerja Pimpinan Daerah Pemerintah Kota Semarang - Muhammad Firman Ghani; Urip Mulyadi (Jurnal Ilmu Sosial dan Humaniora, 2025)
This research is motivated by the role of social media as an effective and interactive means of public communication, with the aim of analyzing the communication strategy of the Public Relations of the Regional Secretariat of the Semarang City Government through Instagram @pemerintahkotasemarang in publicizing the performance of regional leaders. The research uses the framework of communication strategy stages, namely Fact Finding, Planning and Programming, Taking Action and Communication, and Evaluating the Program, combined with James E. Grunig's Theory of Excellence and the Cyber Public Relations (CPR) approach. The results of the study show that Instagram is optimally utilized through various features such as photos, short videos, infographics, stories, reels, and live sessions to display a positive image of regional leaders. The communication strategy is implemented reflecting the Publicity, Public Information, Two-Way Asymmetrical, and Two-Way Symmetrical models, with CPR support to increase transparency, public participation, and evaluation of data-driven content. In conclusion, Instagram has proven to be effective in building a leadership image that is responsive, open, and close to the community. However, this study still has limitations in the form of a limited number of informants and narrow data coverage so that the results cannot be generalized thoroughly. Therefore, follow-up research with a more diverse number of participants and a broader theoretical approach is needed to obtain more comprehensive results.